Hot spot detection and prevention using a simple method in photovoltaic panels. Issue 4 (1st March 2017) - Ghanbari, Teymoor
Abstract : Hot spot in photovoltaic panels has destructive impact on the system, which results in early degradation and even permanent damage of panels. Using conventional bypass diode to prevent hot spotting is not a perfect remedy and more efficient techniques are necessary. In this study, a simple technique is proposed for detection of hot spotting. Also, an efficient method is utilised for protection of the panels against hot spotting. The detection method is based on equivalent DC impedance (EDCI) of the panel's strings, which has useful signatures for hot spot detection. The EDCI monitoring of the panel's strings is performed using a current sensor and several simple resistive voltage dividers. After the detection, hot spotted string is open circuited using a two‐state relay. The performance of the proposed method is confirmed using some experiments. The results confirm high capability of the proposed technique for hot spot detection and protection.